Workforce planning in project-driven companies: a high-level guideline - Micheli, G. J. L.; Martino, A.; Porta, F.; Cravello, A.; Panaro, M.; Calabrese, A. (Frontiers in Industrial Engineering, 2023)
Workforce Planning (WFP) has become a crucial part of the governance of project-driven companies and has been deemed fundamental to drive critical decisions on resource management. This study aims at investigating the current knowledge of the WFP, pointing at the detection of its key factors in terms of process steps, application context, methods, input data, actors, tools and reports’ frequency. Additionally, it attempts to define WFP high-level guidelines which can be generally valid for project-driven organizations. The research seeks to meet these goals by combining the results of the academic literature review on the WFP with the findings of the empirical study in which the representatives of ten project-based enterprises participated. The paper describes the key principles of WFP and its main process’ sections, offering high-level guidelines in terms of recommended process steps, actors involved, operative models, data input, report’s frequency, and tools. The presented features, generated by the literature review and the empirical study, are meant to be generally applicable to project-driven companies and to support the practitioners initiating this process in their organization.